Pengaruh Implementasi Model Project Based Learning (PJBL) Terhadap Motivasi dan Hasil Belajar Siswa di SMK Negeri 5 Sidrap - Sakwati Abidin; Purnamawati; Abdul Muis Mappalotteng (Universitas Negeri Makassar, 2023)
This research is a quasi experimental research with one group pretest posttest design. One Group Pretest-Posttest Design is a research activity that provides an initial test (pretest) before being given treatment, after being given treatment then giving a final test (posttest). Data analysis techniques use descriptive analysis and paired sample T test hypothesis test analysis. The results of the study with descriptive analysis showed that there was an increase in student motivation and learning outcomes from